Part two : The Coptic papyri--codex VII (Codex_Part_II_VII) - Barns, J. W. B.; Browne, Gerald M.; Robinson, James M. (Leiden Boston Brill Academic Publishers, 2012)
With the exception of the exiguous fragments 92c and 93c, this text was first published by R. Kasser, "Fragments du livre biblique de la Genèse cachés dans la reliure d'un codex gnostique," Le Muséon 85 (1972) 65-89; to this article the reader is referred for a detailed treatment of the problems involved. The present re-edition provides a revised transcription, equipped with translation, and the commentary indicates the differences between the new transcript and Kasser's. Throughout we have substituted the more conventional dots for Kasser's half brackets ... these signs he uses for letters which are damaged but certain as well as for those whose reading is in doubt. In the re-edition we employ a dot only where the letter cannot be read with certainty, and we usually do not record the reading of Kasser's text if it differs from ours only in the case of dotted letters
Mode of access: World Wide Web.
Keywords: Nag Hammadi Codices; Gnostic literature; Coptic manuscripts (Papyri)